PENGARUH KEPERCAYAAN, FASILITAS DAN KUALITAS PELAYANAN TERHADAP KEPUASAN NASABAH PT. BPR BKK PURWOKERTO KANTOR CABANG TAMBAK - Susanti, Yulia Eka (E-Prosiding Seminar Nasional Manajemen dan Akuntansi STIE Semarang (SNMAS), 2024)
This study aims to find out more deeply related to: Trust, Facilities, and Service Quality towards Customer Satisfaction. Customer satisfaction is very urgent, especially for financial institutions (banking). The research problem is whether Trust, Facilities, and Service Quality have an influence in determining Customer Satisfaction and the aim is to find out whether Trust, Facilities, and Service Quality have an influence on Customer Satisfaction. The method in this study uses a quantitative approach using multiple linear regression analysis. In this study, the population was new customers of PT. BPR BKK Purwokerto Tambak Branch Office for the period of October 2021, as many as 390 (three hundred and ninety) customers. In the study, samples were taken using slovin and the sample was 80 respondents, sampling using Accidental sampling. Data analysis using multiple regression, t and F hypothesis tests, R square with the help of SPSS application The results of the study based on data processing obtained the results of the t test of the trust factor variable (X1) obtained a t count value of -0.283 and a t table of 1.665. This means that t count <t table while the significance is 0.778 where this value is> 0.05. Therefore, the t count value <t table (-0.283 <1.665) there is no significant influence between the trust factor and customer satisfaction. The facility factor variable (X2) obtained a t count value of 4.715 and a t table of 1665. This means that t count> t table while the significance is 0.000 where this value is <0.05. Therefore, the t count value> t table 4.715> 1.665) there is a significant influence between the facility factor and customer satisfaction. The service quality factor variable (X3) obtained a t-value of 8.442 and a t-table of 1.665. This means that t-value > t-table while the significance is 0.000 where this value is <0.05. Therefore, the t-value > t-table (8.442 > 1.665) there is a significant influence between the service quality factor and customer satisfaction. From the Anova test, the F-value > F-table is 155.128 > 2.72 with a significance level of 0.000. Because the probability (0.000) is much more <0.05, it means that the model is fit. The coefficient of determination can be seen from the R square of 0.860. That the variables of trust, facilities and service quality are able to explain customer satisfaction by 86%, the rest are other variables. Based on the results of the study, PT. BPR BKK Purwokerto Tambak Branch Office needs to pay close attention to the Trust, facilities and service quality factors so that customer satisfaction increases.